Governança corporativa para empresa familiar - Jaeger, Kely Gatti (Universidade do Vale do Rio dos Sinos, 2011)
The advance of competition in all of the economy markets has being demanding companies to have professional businesses, in an increasing way. The family business, beyondthis challenge, still faces particular difficulties, such as the difference among family, business and ownership. Therefore, the aim of this work is to develop a diagnostic for the family group company's JK Inc., of the importance of the implementation of corporate governance, so the organization to reduce their conflicts of interests among family members. To reach a diagnosis, we used specific bibliographies on the subject, questionnaires among family members and on-site observation. After analysis of these data, it was found that the structure of the company has no instrument to resolve internal conflicts, which business decisions are not taken as a whole, which is a lot of power struggle between the family and not have any kind of code of ethics / conduct that guides behavior among family members, helping to reduce these internal conflicts. As consideration, it is suggested the implementation of instruments of corporate governance through a board and a code of ethics in order to settle conflicts of interests among family members, and the perpetuation of the company for future generations.
Keywords: Empresa familiar; Governança corporativa; Código de ética; Conflitos de interesses; Conselho de administração; Family business; Corporate governance; Code of ethics; Conflicts of interest; Board of directors